Hydrogenation of cinnamaldehyde to hydrocinnamaldehyde over Pd nanoparticles deposited on nitrogen-doped mesoporous carbon - Nagpure, Atul S.; Gurrala, Lakshmiprasad; Gogoi, Pranjal; Chilukuri, Satyanarayana V. (RSC Advances, 2016)
Palladium nanoparticles deposited on nitrogen-doped mesoporous carbon (NMC) were synthesized by simple ultrasonic-assisted method. This novel Pd-NMC catalyst was highly active and selective for the hydrogenation of cinnamaldehyde (CA) to hydrocinnamaldehyde (HCA) at room temperature (30 degrees C) under low H-2 pressure. The nitrogen-free mesoporous carbon (MC) and activated carbon (AC) were also employed as the support for Pd in the liquid-phase hydrogenation of CA. The incorporation of nitrogen into carbon matrix remarkably enhanced the catalytic activity and C=C bond hydrogenation selectivity (HCA selectivity of 93% with 100% CA conversion for Pd-NMC) in CA hydrogenation compared to the catalysts with no nitrogen (HCA selectivity of 66 and 47% for Pd-MC and Pd-AC, respectively). Moreover, Pd-NMC catalyst demonstrated an excellent recyclability without any loss in activity and HCA selectivity when it was reused for six times. The superior catalytic performance of Pd-NMC catalyst in CA hydrogenation is attributed to the small size of Pd nanoparticles due to presence of high nitrogen content (11.6 wt%) and mesoporous nature of NMC support.

Aluminium oxide supported on SBA15 molecular sieves as potential lewis acid catalysts for epoxidering opening using aniline - Yadav, Rekha; Muralidhar, Akhila; Shamna, A.; Aghila, P.; Gurrala, Lakshmiprasad; Sakthivel, Ayyamperumal (Catalysis Letters, 2018)
A series of aluminium oxide (Al2O3)-supported SBA-15 molecular sieves were prepared using a one-step wet-impregnation method. Powder X-ray diffraction, nitrogen adsorption/desorption, infrared spectroscopy and ammonia TPD were used to investigate the structures and chemical natures of the surface-bound species. The FT-IR studies of metal-impregnated SBA-15 materials revealed strong covalent interaction of Al2O3 on SBA-15 materials with strong Lewis acidic properties, evident from ammonia-TPD studies. The metal oxide-supported SBA-15 catalysts are active for epoxide ring opening with aniline at room temperature, and showed remarkably high stability and selectivity towards mono-alkylated products (about 86%) viz., 1-(phenylamino)propan-2-ol and 2-(phenylamino)propan-1-ol. The catalytic activities remained intact after several recycles. The observed activities and selectivities were compared with other metal oxide-loaded SBA-15 catalysts obtained by similar preparation methods. Aluminium oxide supported SBA-15 molecular sieves were prepared using a one-step wet-impregnation method. The materials showed strong Lewis acidic sites and promising catalytic activity for epoxide ring opening with aniline at room temperature.

Spinel‐type mixed oxides for stable and selective partial oxidation of benzyl alcohol - Gurrala, Lakshmiprasad; Nagpure, Atul S.; Gurav, Hanmant R.; Chilukur, Satyanarayana (ChemistrySelect, 2018)
Benzaldehyde is an important chemical intermediate, which need to be prepared through an eco‐friendly process. Manganese oxides are active as catalysts for its preparation through partial oxidation of benzyl alcohol. In this study, Cu, Co and Mn containing spinel based mixed oxides (CuxMn3−xO4) were prepared and tested for partial oxidation of benzyl alcohol to get benzaldehyde with high selectivity. The catalytic activity strongly depended on chemical composition, acid‐base properties and oxygen uptake. The influence of chemical composition, reaction temperature, oxygen partial pressure and the weight hourly space velocity (WHSV) were investigated to optimize benzaldehyde yield and to stabilize the catalyst activity. A high benzaldehyde selectivity of 98%, accompanied with benzyl alcohol conversion of 84.5% was obtained over Cu0.25Mn2.75O4 catalyst at 300 °C. It was evident from temperature programmed desorption (TPD) of CO2 that this catalyst was found to have optimum basicity and high oxygen uptake, thus imparting high activity and stability. Activity and catalyst life could be attributed to appropriate acid‐base properties. Supporting Information

New insights into surface functionalization and preparation methods of MWCNT based semiconductor photocatalysts - Joseph, Honey Mary; Sugunan, S.; Gurrala, Lakshmiprasad; Mohan, Mothi Krishna; Gopi, Soumya (Ceramics International, 2019)
The manuscript primarily describes the influence of various synthesis strategies on the photocatalytic properties of MWCNT/TiO2 binary nanohybrids. The multiwalled carbon nanotube modified titania hybrids synthesized via two-step reaction involving the covalent functionalization with green and mild oxidizing agent like H2O2, followed by simple surfactant/template free hydrothermal synthesis exhibited the maximum photocatalytic efficiency. The Total Organic Carbon (TOC) analysis showed complete mineralization of the persistent Rhodamine B dye in about 8 h. These synthesized nanohybrids in varying MWCNT content were tested for their photocatalytic efficiency in the degradation of explosive effluents like 4-nitrophenol and picric acid. The UV-Vis diffuse reflectance spectroscopy (UV-Vis DRS), X-ray photoelectron spectroscopy (XPS), Brunauer Emmett Teller Surface area analysis (BET), Fourier transform infrared spectroscopy (FT-IR), Transmission electron microscopy (TEM) and Raman spectra analysis evidently revealed the effective synergistic interaction between the MWCNT and titania at the interface that has contributed to the significant enhancement of photocatalytic performance.
Keywords: Functionalization; Multiwalled carbon nanotubes (MWCNTs); Nitrophenol (4-NP); Photocatalysis; Picric acid (PA); Rhodamine B (RhB); Sol gel and hydrothermal method; synergistic effects; Titania (TiO2); Total organic carbon content (TOC)

Efficacy of clay catalysts for the dehydration of fructose to 5-hydroxymethyl furfural in biphasic medium - Lucas, Nishita; Nagpure, Atul S.; Gurrala, Lakshmiprasad; Gogoi, Pranjal; Chilukuri, Satyanarayana (Journal of Porous Materials, 2020)
5-Hydroxymethyl furfural (HMF) is one of the important platform chemical obtained from C6 sugars derived from biomass. The efficiency of montmorillonite clay catalysts (K-10, K-20, K-30, and Al pillared clay) has been systematically explored for the synthesis of HMF through dehydration of fructose in a biphasic solvent system. The catalysts were characterized by XRD, N(2)sorption,Al-27 MAS NMR,Si-29 NMR and FT-IR of chemisorbed pyridine. Acid treated K-10 catalyst was found to be the best among the clay catalysts tested. Various reaction parameters such as reaction temperature, catalyst content, solvent were optimized for achieving better yield of HMF. Under optimized reaction conditions, K-10 catalyst affords 80 mol% fructose conversion with HMF yield of 61 mol%. Insight into the type of acid sites essential for such cascade reactions has been furnished. Utilization of clay catalysts for HMF production will be beneficial to improve overall economics for the production of platform chemicals like HMF from biomass-derived raw materials.
Keywords: 5-hydroxymethyl furfural; Acidity; Clays; fructose; Insights

Efficacy of octahedral molecular sieves for green and sustainable catalytic reactions - Lucas, Nishita; Gurrala, Lakshmiprasad; Halligudi, S. B. (Molecular Catalysis, 2020)
Sustainability and Green Chemistry has emerged as catchphrase in modern era and researchers worldwide have embraced it as new paradigm of development. In this context identifying potential materials able to curb multiple grave issues thus contributing towards sustainability is vital. Catalytic materials are quite potent for addressing current social, economic and environmental problems like harnessing alternative energy source, pollution prevention/remediation and manufacturing of commodity chemicals. Thus, the present review accentuates the efficacy of porous octahedral molecular sieves (OMS) as catalyst for such environmentally important reactions. It discusses about structural importance of OMS and their applications for green and sustainable catalytic reactions. Finally, the limitations are highlighted and future perspectives are presented which will ameliorate its catalytic utilization in energy and environmental domains.
Keywords: catalytic transformations; Lignocellulosic biomass; octahedral molecular sieves; platform chemicals; renewable feedstock

Selective production of C9 monomeric phenols via hydrogenolysis of lignin using Pd-(W/Zr/Mo oxides)-supported on biochar catalyst - Gurrala, Lakshmiprasad; Kumar, M. Midhun; Sharma, Shweta; Paek, Changyub; Vinu, R. (Fuel, 2022)
Valorizing lignin to phenolic monomers and fine chemicals is an essential component of a sustainable biorefinery that uses lignocellulosic feedstocks. In this study, Pd-metal oxides (ZrO2, WOx, MoO3) supported on activated biochar (ABC) catalysts were developed for hydrogenolysis of lignin. The metals (2% Pd, 5% Zr, 5% W, 5% Mo) were supported on activated biochar using the wetness impregnation method, and the catalysts were extensively characterized. The effect of addition of secondary metals on active surface properties such as acidity, Pd metal particle size and dispersion were also evaluated. The selectivity to C9 monomeric phenols followed the trend: 2Pd-5Mo/ABC (57.3%) > 2Pd-5Zr/ABC (49.2%) > 2Pd-5W/ABC (45%) > 2Pd/ABC (42.9%). The maximum C9 phenolic monomer yield achieved in this study was similar to 22 wt%. The fractional conversion of lignin was 67-69% with Pd-metal oxide catalysts. The presence of Mo in the catalyst inhibited the hydrogenation of aliphatic C-alpha = C-beta in lignin and led to the formation of t-isoeugenol, while the presence of W and Zr resulted in selective formation of the hydrogenated product, propyl guaiacol. Using model compounds, it is proved that the formation of propyl guaiacol is via hydrogenation of t-isoeugenol, and not through dehydroxylation of propanol guaiacol. The dehydroxylation activity of the catalysts is attributed to the higher Lewis acidity and electropositive nature of the metals. A notable carbon atom economy of 47-50% towards total phenolic monomers was achieved with 2Pd/ABC, 2Pd-5Mo/ABC and 2Pd-5Zr/ABC catalysts.
Keywords: Activated biochar; Guaiacol; Hydrogenolysis; lignin; Metal oxides; Palladium

One-pot production of liquid hydrocarbons by catalytic hydrodeoxygenation of lignocellulosic biomass using nickel loaded on zeolite-based supports - Siakpebru, Odiri K.; Uchagawkar, Anoop; Gurrala, Lakshmiprasad; Bartlett, Jared; Adamson, Piersen; Gorschak, Nicholas; Hassiba, Adam; Niphadkar, Prashant; Bokade, Vijay; Morais, Ana Rita C. (Energy & Fuels, 2024)
The synthesis of liquid hydrocarbons from lignocellulosic biomass has been achieved with notable success. However, these technologies often require multistep approaches and are energy intensive. Thus, there is a considerable economic and environmental benefit of process intensification by the synthesis of liquid hydrocarbons in a one-pot process. For the first time, we report direct conversion of raw poplar into liquid alkanes and aromatics (carbon yield of 15.6 +/- 0.6 wt %) with high selectivity toward C-7-C15 cycloalkanes (7.8 +/- 0.1 wt %) and low level of oxygenated compounds (<2.0 wt %) at 270 degrees C and 3 MPa initial H(2 )pressure for 6 h using 10% Ni/H-beta zeolite as a catalyst and cyclohexane as a solvent. The effect of temperature (250-270 degrees C), Ni loading (0-10%), and type of zeolite support (H-beta, ZSM-5, and USY) on process performance was also investigated. In addition, the 10% Ni/H-beta catalyst showed recyclability over two reactions, with a 17.6% decrease in liquid hydrocarbon yield after the first reaction. This approach has the potential to simplify the synthesis of liquid fuels from lignocellulosic biomass.